2023
DOI: 10.2459/jcm.0000000000001530
|View full text |Cite|
|
Sign up to set email alerts
|

Serum albumin and prognosis in elderly patients with nonischemic dilated cardiomyopathy

Abstract: Aims Hypoalbuminemia was extensively used to diagnose malnutrition in older adults. Malnutrition was associated with mortality in elderly patients with cardiovascular diseases. The relationship between hypoalbuminemia and clinical outcomes in elderly patients with nonischemic dilated cardiomyopathy (NIDCM) remains unknown. Methods A total of 1058 consecutive patients with NIDCM (age ≥60 years) were retrospectively enrolled from January 2010 to December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…In patients with hypoproteinemia caused by disease or diet, nutritional deficiency in local skin tissues is not conducive to cell growth and wound healing. 18 In the present study, we found that Lac level was significantly associated with the occurrence of pressure ulcers. Lac is a key product of human glucose metabolism and anaerobic cell metabolism.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In patients with hypoproteinemia caused by disease or diet, nutritional deficiency in local skin tissues is not conducive to cell growth and wound healing. 18 In the present study, we found that Lac level was significantly associated with the occurrence of pressure ulcers. Lac is a key product of human glucose metabolism and anaerobic cell metabolism.…”
Section: Discussionsupporting
confidence: 57%
“…In patients with hypoproteinemia caused by disease or diet, nutritional deficiency in local skin tissues is not conducive to cell growth and wound healing. 18…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly with severe AS, numerous factors such as prolonged inflammation, appetite loss, decreased physical capacity, reduced muscle mass, impaired mental functions, and coexisting comorbidities often contribute to malnutrition. Hypoalbuminemia, a marker of malnutrition, is associated with increased in-hospital and long-term mortality in patients with dilated caridyomyopathy 34 . This nutritional deficiency markedly increases frailty in patients, adversely impacting their prognosis.…”
Section: Discussionunclassified
“…The following funding statement of this paper should have appeared in this paper by Li et al 1 . This was removed in error before final publication.…”
mentioning
confidence: 99%